Inhibition of estrogen-independent mammary carcinogenesis by disruption of growth hormone signaling - Zhang, Xiao; Mehta, Rajendra G.; Lantvit, Daniel D.; Coschigano, Karen T.; Kopchick, John J.; Green, Jeffrey E.; Hedayat, Samad; Christov, Konstantin T.; Ray, Vera H.; Unterman, Terry G.; Swanson, Steven M. (Carcinogenesis (New York), 2007)
Clinical trials and laboratory-based studies indicate that the growth hormone/insulin-like growth factor-I axis may affect the development of breast cancer. The purpose of the present investigation was to develop a genetic model of mammary cancer to test the hypothesis that downregulation of GH signaling can substantially retard mammary cancer progression. We crossed the Laron mouse, in which the gene for the GH receptor/binding protein has been disrupted, with the C3(1)/TAg mouse, which develops estrogen receptor α negative mammary cancers. All mice used in our experiments were heterozygous for the large T antigen (TAg) and either homozygous wild-type for GHR (Ghr+/+) or null for GHR (Ghr−/−). Compared with the TAg/Ghr+/+ mice, the TAg/Ghr−/− mice showed delayed mammary cancer latency with significantly decreased multiplicity (9.8 ± 1.4 versus 3.2 ± 1.2) and volume (776.1 ± 284.4 versus 50.5 ± 8.9 mm3). Furthermore, the frequency of mammary hyperplasias was significantly reduced in the TAg/Ghr−/− mice (15.0 ± 1.7 versus 6.8 ± 1.7). To establish that these mammary cancers were estrogen-independent, 12-week-old TAg/Ghr+/+ mice, which lack visible hyperplasia, were either ovariectomized (ovx) or sham operated (sham). Compared with the sham group, ovariectomy resulted in no difference in the frequency of mammary hyperplasia, mammary tumor latency, incidence, multiplicity or tumor size. Together, these data demonstrate that the disruption of GH signaling significantly retards TAg-driven mammary carcinogenesis, and suggest that disrupting GH signaling may be an effective strategy to inhibit the progression of estrogen-independent breast cancer.